Who Cares for Care Leavers?. Issue 175 (September 2016) - Askew, Julie; Rodgers, Paul; West, Andrew
Abstract : This chapter describes a programme of learning and development at the University of Sheffield, United Kingdom, to support looked‐after children and care leavers (youth previously provided care outside or beyond family) throughout the student lifecycle. In this context, looked‐after children are those cared for by a town/city authority where parent(s) are not able to provide suitable care.